Baking Soda and Peroxide Formulation as Dental Whitening Gel - Herma Fanani Agusta; Alfian Syarifuddin; Fitriana Yuliastuti; Misya Putri Kurnia Pradani (Konsorsium LPPM Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Indonesian society began to make appearance as a primary need. Appearance becomes important for middle and upper social classes which reaches 60-70% in Indonesia. Researchers are trying to find a combination formula of two teeth whitening ingredients (Baking Soda and Peroxide). The study uses an experimental method, which is to make a dental gel with variety of gradient constituent formulas, including F1, F2, F3, F4, and F5. F5 is the most optimal formula with best stability test results among other. F5 with Peroxide concentration of 30% had teeth whitening activity of 38% by two months in vitro test on adult teeth samples.